Stereo 3D Mouse Cursor: A Method for Interaction with 3D Objects in a Stereoscopic Virtual 3D Space - Hossein Azari; Irene Cheng; Anup Basu (International Journal of Digital Multimedia Broadcasting)
We introduce a different approach of applying stereoscopy principles to implement a virtual 3D pointing technique called stereo 3D mouse cursor (S3D-Cursor) based on two or more views of an ordinary mouse cursor. The basics of such an idea have already been applied as a by-product of some stereo-based visualization applications with usually less attention to its strengths or weaknesses as a generic alternative of its 2D counterpart in stereoscopic 3D space. Here, we examine if such an idea satisfies all or the main expected requirements of an abstract 3D cursor. Moreover, we analyze its accuracy and evaluate the applicability of this approach in terms of different efficiency factors. For this purpose, we have adapted a real-time point-based rendering software called QSplat to a multiview rendering version named QSplatMV. We have implemented the S3D-Cursor on top of this new application and developed a simple editing toolset for manipulating the virtual 3D objects. Our user evaluation results suggest the effectiveness of the approach in terms of detection accuracy and user satisfaction compared to using an ordinary mouse cursor on a conventional 2D screen.